Equity in health: Comparison of children health indices in poor and rich zones - Reza Saeidi; Vahid Sadeghi (Mashhad University of Medical Sciences, 2015)
Background: Although many efforts made for the advancement of medical science, it is distributed inequitably despite of all existing financial and human resources facilities. Children as the most important and vulnerable groups of society are influenced by these inequities. The Objective of this study is comparison of children health indices in rich and poor rural zones in Mashhad/Iran. Methods: This is a cross sectional study, We considered a poor (Andad) and a rich (Toos) zones to compared for some health indices. We compared some indices like: maternal mortality rate (MMR), neonatal mortality rate (NMR), children under 1 (IMR) and under 5 years mortality rate (U5MR), low birth weight prevalence (LBW), exclusive breast feeding (EBF) and fertility rate. Data collected with check list and analyzed by SPSS-11.5. Results: in our study in two poor (Andad) and rich (Toos) zones we have: Neonatal mortality rate (zero versus 5.46) (P=0.00); breast feeding indices like exclusive breast feeding indices up to 6 month (54.4% versus 79%) (P=0.01); have significant differences between two zones. But fertility rate indices like total fertility rate (2.09 versus 1.95) (p=0.98) and Mean children mortality rates during 2011-2013 like children less than 5 years mortality (18.65 versus 12.13 per thousand live birth) (p=0.29) does not have statistically significant differences. Conclusion: This study shows that health indices in rich and poor zones, have significant differences